Income Statement Pentacode Digital (Using Business Model Canvas) - Genia Fatihat, Gita; Yuliani, Reva; Oktaviani, Desy; Sutisna, Deden; Hasan Padmanegara, Oliver (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe the business model in Pentacode Digital and its current strengths, weaknesses, opportunities and threats in it to be able to propose a new business model canvas. The method used is descriptive method. The method used is qualitative methods and modeling. And technique of the data used by other interviews, a questionnaire, and observation.The results show that the picture of the business model now is nine blocks of the business model canvas Pentacode Digital has a weakness in the block channels, revenue streams, and key activities. While, Pentacode Digital has a strength in the cost structure, value propositions, customer relationships, key patnerships, and customer segments. The new business model for the Pentacode Digital is by adding product content, optimizing channels, and increasing revenue streams